Development of DiabecineTM tablet and confirmation of its physical properties and pharmaceutical safety analysis - Chee, Teh Liam; Fadzilah Adibah Abdul Majid,; Mohd Cairul Iqbal, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Herbal medicine is usually made using dry powdered herbs in the form of capsule. Capsule form herbal supplement suffers lower shelf life as compared to compact herbal powder in tablet form. In this study, Diabecine™, a blend of herbal medicine traditionally used as herbal supplement for diabetic patients was selected and transformed into a compressed tablet. Direct compression method and minimal usage of excipients were the aims of this study. By using direct compression, the blend of 40% fine powder herbs and 60% of excipients performed the best and fulfill the pharmaceutical standard. The safety data of microbial and heavy metal testing obtained met the safety requirements for herbal supplement category under the National Pharmaceutical Control Bureau of Malaysia. In conclusion, the tablet formulation of DiabecineTM is suitable to be manufactured by using direct compression method. This research implicates the possibility of producing tablets with high dose of herbal powder by direct compression method.